American Black Nightshade Biology and Control in Fruiting Vegetables, Cucurbits, and Small Fruits - Andrew W. MacRae (EDIS)
HS1176, a 3-page illustrated fact sheet by Andrew W. MacRae, describes this weed common in fruiting vegetable fields, cucurbit, and strawberry production — classification, seedling identification, mature plant, management considerations, and chemical control. Includes reference. Published by the UF Department of Horticultural Sciences, May 2010.